2016
DOI: 10.3847/0004-6256/152/6/202
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Dynamics and Star Formation in the Nearby Dwarf Galaxy NGC 5238

Abstract: We present new H I spectral line images of the nearby low-mass galaxy NGC 5238, acquired with the Karl G. Jansky Very Large Array (VLA a ). Located at a distance of 4.51 ± 0.04 Mpc, NGC 5238 is an actively star-forming galaxy with widespread Hα and UV continuum emission. The source is included in many ongoing and recent nearby galaxy surveys, but until this work the spatially resolved qualities of its neutral interstellar medium have remained unstudied. Our H I images resolve the disk on physical scales of ∼40… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…NGC5238: Classified as SABdm in NED, this galaxy belongs to the Canes Venatici I group. From the HI perspective, Cannon et al (2016) found that the HI disk is asymmetric in the outer regions, and the HI surface density maximum is not coincident with the central optical peak, but rather is offset to the North-East by ∼ 300 pc. Our maps suggest that the iso-contours of the young population are also twisted with respect to the RGB ellipse.…”
Section: Sf Spatial Patternsmentioning
confidence: 99%
“…NGC5238: Classified as SABdm in NED, this galaxy belongs to the Canes Venatici I group. From the HI perspective, Cannon et al (2016) found that the HI disk is asymmetric in the outer regions, and the HI surface density maximum is not coincident with the central optical peak, but rather is offset to the North-East by ∼ 300 pc. Our maps suggest that the iso-contours of the young population are also twisted with respect to the RGB ellipse.…”
Section: Sf Spatial Patternsmentioning
confidence: 99%
“…In the first line of investigation we apply the spatially resolved position-velocity analysis developed in Cannon et al (2011b) and employed in McNichols et al (2016) and Cannon et al (2016). This technique allows us to estimate the projected rotation velocity of a source when its kinematics are not well described by a simple tilted ring.…”
Section: Spatially Resolved Position-velocity Analysismentioning
confidence: 99%
“…For consistency with the results presented in Teich et al (2016) and Cannon et al (2016), we use both values of inclination for each galaxy in the discussion that follows. The lower inclinations dervied using the HST images compared to those using the ground-based images can be attributed to the different surface brightness sensitivities of the two sets of images, and also in part to the differences in the methods applied to excise foreground and background objects.…”
Section: Discussionmentioning
confidence: 98%